Application of Satellite Image Processing Methods for Hydrocarbon Field Search - Fiodortsev R.V.; Silie Cuenca A.R.; Kozhevnikov D.A.; Medina V.M.; Delgado R. (Белорусский национальный технический университет, 2019)
The object of the study is software methods of the Earth surface images processing obtained from the VRSS-2 satellite to determine the spectral composition of the vegetation cover to detect the presence of carotenoids during prolonged exposure to hydrocarbons. The photosynthetic pigments of higher plants (chlorophylls, carotenoids and phytobiliproteins) were analyzed. In the chloroplasts of higher plants, chlorophyll and carotenoids are present in a ratio of about 3:1. The presence of hydrocarbons increases the amount of carotenoids. Carotenoids have absorption bands in the blue-violet region from 400 to 500 nm and a high reflection coefficient in the red-orange and yellow spectral regions, which corresponds to the multispectral MSS operating mode (B2) of the VRSS-2 satellite camera. An analysis of the vegetation growing in the study area of the Puerto Kumarebo settlement showed that the best indicator of the presence of hydrocarbons in the soil is Prosopis juliflora – CUJI with a deep root system of up to 50 m, growing in the study area. Using ENVI software, a comparative evaluation of the efficiency of photographs image processing was carried out using the normalized relative vegetation index (NDVI) and the structure-insensitive pigment index (SIPI) to detect changes in the color of green vegetation. It has been established that the SIPI index is more applicable for hydrocarbon search tasks. Moreover, the recorded index fluctuations in the area of uniform vegetation at the level of 2.5 % are characteristic of normal growing conditions and cannot serve as evidence of the presence of factors indicating the presence of hydrocarbons in the soil. For a more detailed assessment of the presence of carotenoids in the foliage and the presence of hydrocarbons in the soil, photographs with high optical resolution of objects on the surface are required.
Keywords: carotenoids; hydrocarbons; photographs; satellite; ENVI; каротиноиды; углеводороды; фотографии; спутник; ENVI; 535.015, 535.422